2016
DOI: 10.1186/s12883-016-0730-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of the Status Epilepticus Severity Score (STESS) and its components for long-term survival

Abstract: BackgroundThe “Status Epilepticus Severity Score” (STESS) is the most important clinical score to predict in-hospital mortality of patients with status epilepticus (SE), but its prognostic relevance for long-term survival is unknown. This study therefore examined if STESS and its components retain their prognostic relevance beyond acute treatment.MethodsOne hundred twenty-five non-anoxic patients with SE were retrospectively identified in two hospitals between 2008 and 2014 (39.2 % refractory SE). Patients’ tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 23 publications
4
44
0
2
Order By: Relevance
“…Interestingly, both new scoring systems STESS and EMSE-EACE that have been designed to predict SE mortality were indeed found to be associated with outcome in the univariate analysis of our study. Several previous studies have found a significant association between STESS and outcome [7,19]. Only a few studies have evaluated both STESS and EMSE, and have found, as in our study, a stronger association for EMSE-EACE than for STESS [21,41].…”
Section: Factors Associated With Outcomesupporting
confidence: 66%
See 1 more Smart Citation
“…Interestingly, both new scoring systems STESS and EMSE-EACE that have been designed to predict SE mortality were indeed found to be associated with outcome in the univariate analysis of our study. Several previous studies have found a significant association between STESS and outcome [7,19]. Only a few studies have evaluated both STESS and EMSE, and have found, as in our study, a stronger association for EMSE-EACE than for STESS [21,41].…”
Section: Factors Associated With Outcomesupporting
confidence: 66%
“…Moreover, the factors that lead to refractoriness and that determine outcome in SE are still insufficiently elucidated. Two new clinical scoring systems have emerged for the prediction of mortality in SE, Status Epilepticus Severity Score (STESS) [15,16] and Epidemiology based Mortality score in SE (EMSE) [17], but studies have shown that they are better at predicting survival than death, with high negative predictive values and low positive predictive values [15,[17][18][19][20]. No such validated scoring systems currently exist for the prediction of refractoriness, and various factors like low level of consciousness before treatment, acute symptomatic etiologies, age, non-convulsive SE in coma, absence of previous seizures, low levels of serum albumin at SE onset and periodic discharges on EEG have been found to be associated with refractoriness in different studies [4][5][6][7]21].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for mortality in adults include etiology (progressive, remote, or acute symptomatic causes),8, 12, 13, 24, 55 older age,11, 12 SE duration,8, 13, 56 and development of subsequent epilepsy 11. The Status Epilepticus Severity Score is a valuable tool to assess in‐hospital mortality but has not been clearly validated to estimate long‐term mortality 57, 58, 59. The Epidemiology‐Based Mortality in Status Epilepticus score considers etiology, age, electroencephalogram, and comorbidities and has been associated with poor long‐term outcome in one prospective study 19…”
Section: Long‐term Outcomes Of Sementioning
confidence: 99%
“…11 The Status Epilepticus Severity Score is a valuable tool to assess in-hospital mortality but has not been clearly validated to estimate long-term mortality. [57][58][59] The Epidemiology-Based Mortality in Status Epilepticus score considers etiology, age, electroencephalogram, and comorbidities and has been associated with poor long-term outcome in one prospective study. 19…”
Section: Mortalitymentioning
confidence: 99%
“…Among 468 retrieved studies, ten studies on the development or validation of prognostic scales in SE were included after screening titles and abstracts (Figure 1). [6][7][8][9][10][11][12][13][14][15] A total of 4 prognostic scores have been proposed to date: the Status Epilepticus Severity Score (STESS), 6,7 the Epidemiology-based Mortality score in Status Epilepticus (EMSE), 8 the modified STESS (mSTESS), 9 and the Encephalitis Nonconvulsive Status Epilepticus Diazepam Resistence Imaging Tracheal Intubation (END-IT) score, 10 the latter of which was developed by our group.…”
Section: Introductionmentioning
confidence: 99%